A novel method of combined phacoemulsification and vacuum trabeculoplasty ab interno - V. N. Trubilin; N. A. Kaira (Oftalʹmologiâ, 2014)
Aim. To improve the efficacy of cataract and primary open-angle glaucoma (POAG) surgery using a novel combined surgical technique.Materials and methods. 219 patients were included in the study. According to the design, all subjects weredivided into study group (n = 58) and two control groups (n = 78 and n = 83). Combined phaco and vacuum trabeculoplasty (VTP) ab interno was performed in 58 study group patients. Pre-op and post-op, all patents had a complete eye examination including vision and hydrodynamics testing as well as anterior chamber depth (ACD) and angle assessmentusing optical coherent tomography.Results. In study group, stable IOP decrease was observed for 2‑yrs follow-up. Phacoemulsification in cataract and POAG patients has an impact on anterior segment anatomy and topography owing to significant increase of ACD by 1.2 mm and anterior chamber angle by 3.3°. VTP ab interno provides additional ACD increase by 1.8 mm and anterior chamber angle by 15.9°. Complication rate was 8.5 % in study group (i.e., following combined phaco and VTP ab interno) and 5.1 % and 8.4 % in control groups. Hospitalization days in all groups had no significant differences.Conclusion. A novel method of combined VTP ab interno and cataract phacoemulsification provides significant IOP decrease (by 74 %) at 2‑yrs follow-up. Following VTP and phaco, fewer or even no hypotensive eye drops were required. This technique is less traumatic than traditional cataract and glaucoma surgery. Indication for combined VTP and phaco is (im) mature cataract with medically (sub) compensated POAG.